Bibliometric Analysis of Islamic Higher Education (West Science Islamic Studies, 2026)
Islamic higher education has become an increasingly important research area due to its role in integrating religious values, academic development, technological advancement, and social transformation. This study aims to explore the global research development, intellectual structure, collaboration patterns, and emerging themes in Islamic higher education through a bibliometric analysis approach. Data were retrieved from the Scopus database using relevant keywords related to Islamic higher education, and the collected publications were analyzed using bibliometric techniques with VOSviewer. The analysis covers publication trends, influential authors, institutional and country collaborations, citation performance, keyword co-occurrence, and thematic evolution. The findings reveal that research on Islamic higher education has expanded significantly, with Indonesia emerging as the most productive and influential contributor, followed by Malaysia and other countries with active scholarly engagement. Citation analysis indicates that major contributions focus on educational technology, Islamic educational philosophy, leadership, curriculum development, and the relationship between Islamic traditions and modern educational practices. Keyword analysis demonstrates a transition from conventional themes related to Islamic studies and religious education toward contemporary issues such as artificial intelligence, digital learning systems, religious moderation, and educational innovation. This study highlights that Islamic higher education has evolved into a multidisciplinary research field that connects religious knowledge with broader educational, technological, and societal challenges. The findings provide valuable insights for researchers, policymakers, and educational institutions in identifying future research directions and strengthening the global development of Islamic higher education.